Failure of Senior Literature Students to Write Academic Research Projects at the English Department of College of Languages in Salahaddin University-Erbil - Balaky, Saman Salah Hassan (Zanco Journal of Human Sciences, 2021)
Problems with writing academic research by the senior literature students of the English department of the college of languages at Salahaddin University in Erbil have been occurring literally since the establishment of this department. Students face many difficulties while setting out to write research projects which are part of their graduation requirements. They usually feel frustrated at the beginning stages and struggle with their research title, outline and structure. Graduation research has been a big challenge for the department and teachers, too. It becomes a controversial topic every new academic year, and discussions around it conclude with either removing this subject from the department curriculum for fourth-year students or actions to be taken up to improve its existing situation and mechanisms of conducting it. This research study is an attempt at looking at the problems surrounding this subject at the English department, going to the roots of these problems and finding relevant solutions so the situation changes for the better and students face fewer problems with their research works.